American Exceptionalism from Unilateralism to Decline - LAHLOUH, Amel (The Notebooks of the Algerian Poetics Laboratory Journal, 2022)
The present paper deals with American Exceptionalism from unilateralism to decline. After World War II, the rise of the United States to superpower status exaggerated its self-perceived virtuosity in world affairs, which generated more acts of unilateralism in its foreign relations and international law attitudes. Yet in recent years however many have suggested that the United States might be losing its edge in world affaires. Increasing economic power of China during the recent decades alonside with the declining share of the United States in the global production and international trade in the beginning of the 21st Century has led to a change in the geopolitical landscape of the world and emergence of the group of two, or simply G2.